Debilitating Manifestation of a Disease with Multiple Names: A Severe Case of Sclerosing Mesenteritis - Valeriia Klymenko; Reba Varughese; Katherine A Woolley; Joseph M Wetherell; Haritha Mopuru; Edward Mensah; Imran Siddiqui (Case Reports in Gastrointestinal Medicine)
Sclerosing mesenteritis (SM) is a rare inflammatory condition with unknown etiology that affects the mesenteric adipose tissue. We present a case of a 49-year-old male with severe abdominal pain who underwent abdominal biopsy confirming the presence of adipose inflammation and necrosis. The diagnosis of SM was made, and the patient was treated with prednisone and tamoxifen. As this condition is rare, there are no standard guidelines for management. This case aims to outline a possible treatment plan.